Entrepreneurship Education Strategy at Salaf Islamic Boarding School: Case Study at Pesantren Darul Muttaqien Kendal - Nasirudin Nasirudin; Mustopa Mustopa; Nasikhin Nasikhin; Abdul Razak Abdulraya; Farhah Binti Saefudin (Ta'dib, 2023)
This study aims to execute the entrepreneurship education strategy implemented by Salaf Islamic boarding schools. This qualitative research collects data through interviews, observation, and documentation studies. Data were analyzed using the Miles and Huberman models. This research shows that the alleged educational pattern of the Salaf Islamic boarding schools which ignores worldly problems, in fact has a very systematic pattern of entrepreneurship education. The results of this study provide a clear explanation of how the entrepreneurship education system in Islamic boarding schools is very well coordinated. Santri who are at the age of children are given educational provisions in the character of honesty, leadership, understanding opportunities, and cooperation so that they are able to become entrepreneurs who bring benefits to all people. Interestingly, this kind of character education is delivered in Islamic ways, namely using the study of arba'in hadiths. Considering that entrepreneurship character education alone is not enough to produce talented entrepreneurs, students who are in their teens are also given training to be able to choose good raw materials, understand how and what objects must be produced, and even learn to market their products within the pesantren. Apart from that, the pesantren also provides facilities for adult students to master marketing techniques, with the aim that the products produced can be in demand and known by the wider community. The contribution of this research can be used as a guideline for Islamic boarding schools to formulate policies so that entrepreneurship education programs can be implemented optimally in Islamic boarding schools.